Enako plačilo za enako delo ali delo enake vrednosti v praksi - Poje, Andreja (Teorija in praksa, 2019)
The article discusses inequalities in pay between women and men in Slovenia, considering three selected occupations between 1999 and 2015. Despite the widespread belief there are no gender pay gaps in Slovenia, the analysis reveals differences in women and men's income, especially when comparing the same educational attainment and experience, and at the workplace level. In the period 2010-2015, women in Slovenia on average earned 6.2 percent less than men and 11.9 percent less at the same workplace. In the same period, at the level of the population women with equal educational attainment and experience earned almost 20 percent less than men, and 14 percent less at the workplace level. Men's average income in all three analysed occupations and in all years exceeds the average income of women; the gender pay gap in the observed occupations and its movements up or down over time vary among the occupations. The results of the analysis provide a useful starting point for further research into what causes the gender pay gap.
Keywords: Enako plačilo za enako delo; Equal pay for equal work; Gender inequality; moški; Plače; policija; razlike v plačilu; spol; Spolna neenakost; visoko šolstvo; Wages; zdravstvo; ženske